The Importance of Social Networking in the Dissemination of Musical Contents and Musical Events: The Case of Facebook in Portugal - Passos, J.; Alturas, B.; Laureano, Raul M. S. (LCBR European Marketing Conference 2012, 2012)
This paper studies the importance of social networks in the dissemination of musical contents and musical events, studying the specific case of Facebook in Portugal. The theoretical framework reveals a new technological and social reality, which leveraged a profound change in how we perceive and consume musical contents. The paradigm shifts and new opportunities provided by the digital context are particularly relevant in the music industry, which has been forced to reinvent itself in recent years due to the decreasing revenues from the sales of musical content. A methodology is proposed which will first frame the current situation of the Portuguese music industry through several interviews to some of its stakeholders, following an online survey which will characterize the Facebook user in general and its sharing habits of musical content and musical events. The results suggest that Facebook is used in the discover and follow of musical artists, with the sharing of musical content being a common phenomenon among its users. It is also perceived that the dissemination of musical events has a practical effect on the attendance of concerts and music festivals. Therefore, it is concluded that Facebook is a platform where consumers share their musical contents and events, where they search for their favorite artists and also find new artists, thus constituting a platform that should be intelligently exploited in a marketing perspective, taking into account the characteristics of a new type of consumer and a new kind of attitude towards music.